A Survey of International Public Sector Accounting Standards - Dr. M. R. Prakash; Mrs. G. Madhuri; Ms. K. Agilandeswari (HM Journals, 2022)
Globalization generates a verifiable upheaval and unavoidably impacts the bookkeeping division. Thus, harmonization of national bookkeeping frameworks meets with accomplishment under globalization. Bookkeeping techniques for neighbourhood open parts can't be unaffected and International Public Sector Accounting Standards (from this time forward IPSAS) have been gotten for a worldwide appropriation. This study delineates the huge way of IPSAS, their general qualities and importance of them. Additionally, cash‐basis and accrual‐basis measures will be called attention to. Moreover, this study will allude to some theoretical issues about IPSAS, as a type of question to some of their thoughts and objectives.